Inovasi Bahan Ajar Teks Narasi Bahasa Indonesia SD Berbasis Mobile Module “EMONAKU” dengan Pendekatan CRT Kearifan Lokal Kudus - Rani Setiawaty; Lintang Kironoratri; Luthfa Nugraheni; Riyadi Widhiyanto (Universitas Ngudi Waluyo, 2026)
This study aims to develop and test the validity of the Mobile Module-based teaching material “EMONAKU” (E-Module: Narrative Text based Local Wisdom on Kudus) as a narrative text teaching material for Indonesian language based on local wisdom in Kudus using the Culturally Responsive Teaching (CRT) approach for elementary school students. The research used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques included questionnaires, interviews, documentation, and narrative text comprehension literacy tests through a pretest-posttest design. The data were analyzed descriptively to assess the validity and practicality of the product, and statistically using a paired-sample t-test to assess the product’s effectiveness. The results showed that the EMONAKU Mobile Module as teaching materials was rated as highly valid based on the assessments of media experts (86%), language experts (90%), and subject matter experts (88%). The practicality test showed an 82% student response rate, which is considered highly practical. The effectiveness test results showed a significance value of 0.000 (<0.05), indicating a significant increase between the students' pretest and posttest scores. Furthermore, calculations of the effect size using the Effect Size Calculator yielded a Cohen’s d value of 1.290, which falls into the large category, indicating that the intervention had a strong effect on improving students’ narrative text comprehension literacy. These findings indicate that EMONAKU is effective in improving narrative text comprehension literacy, particularly in terms of content comprehension, determining main ideas, summarizing stories, and relating text content to local cultural values. Abstrak Penelitian ini bertujuan untuk mengembangkan dan menguji kevalidan bahan ajar berbasis Mobile Module “EMONAKU” (E-Modul Teks Narasi Kearifan Lokal Kota Kudus) sebagai bahan ajar teks narasi Bahasa Indonesia berbasis kearifan lokal Kudus dengan pendekatan Culturally Responsive Teaching (CRT) pada siswa sekolah dasar. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Teknik pengumpulan data meliputi angket, wawancara, dokumentasi, serta tes literasi pemahaman teks narasi melalui desain pretest–posttest. Data dianalisis secara deskriptif untuk menguji validitas dan kepraktisan produk, serta secara statistik menggunakan uji paired sample t-test untuk menguji efektivitas produk. Hasil penelitian menunjukkan bahwa bahan ajar berbasis Mobile Module “EMONAKU” memperoleh kategori sangat valid berdasarkan penilaian ahli media (86%), ahli bahasa (90%), dan ahli materi (88%). Uji kepraktisan menunjukkan respon siswa sebesar 82% dengan kategori sangat praktis. Hasil uji efektivitas menunjukkan nilai signifikansi 0,000 (<0,05), yang menandakan adanya peningkatan signifikan antara nilai pretest dan posttest siswa. Adapun, berdasarkan perhitungan ukuran efek dengan bantuan Effect Size Calculator menunjukkan nilai Cohen’s d sebesar 1,290 yang termasuk dalam kategori besar, sehingga mengindikasikan bahwa perlakuan yang diberikan memiliki pengaruh yang kuat terhadap peningkatan literasi pemahaman teks narasi siswa. Temuan ini menunjukkan bahwa EMONAKU efektif dalam meningkatkan literasi pemahaman teks narasi, khususnya pada aspek pemahaman isi, penentuan ide pokok, penyimpulan cerita, dan pengaitan isi teks dengan nilai budaya lokal.